The Optimal Turnover Threshold and Tax Rate for SMEs - Wei, Feng (IMF Working Papers; Working Paper, 2019)
Presumptive income taxes in the form of a tax on turnover for SMEs are pervasive as a way to reduce the costs of compliance and administration. We analyze a model where entrepreneurs allocate labor to the formal and informal sectors. Formal sector income is subjected either to a corporate income tax or a tax on turnover, depending on whether their turnover exceeds a threshold. We characterize the private sector equilibrium for any given configuration of tax policy parameters (corporate income tax rate, turnover tax rate, and threshold). Given private behavior, social welfare is optimized. We interpret the first-order conditions for welfare maximization to identify the key margins and then simulate a calibrated version of the model.